Tari Barong: Pergulatan Sakral dan Profan (Tinjauan Teologis, Estetis, dan Etis) - I Wayan Sunampan Putra (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The existence of Hinduism is contained in (tattwa, Susila, upakara) Hinduism is also inseparable from religious art, meaning that art is always used in the realization of religious ritual activities, this gives birth to sacred art which is usually used in religious ritual implementation or used to accompany the process of religious ceremonies. . One of the sacred arts that is often used in religious ceremonies is the barong dance. Even the barong dance has various types such as the barong ket dance, barong bangkung, barong brutuk, barong landung and so on. However, along with the development of the era of sacred dance, there has also been a change in the placement, sometimes sacred art is used in the profane realm or is only used for entertainment for material purposes. Like wise with the barong dance which is often performed in the realm of propane such as the world of entertainment tourism and so on. This is what makes a barong dance struggle whether sacred or profane. Through this article, the barong dance will be studied and described from the viewpoint of aesthetics, theology and ethics.